AN ANALYSIS OF DOG FAT IN BEEF MEATBALLS USING FOURIER-TRANSFORM INFRARED SPECTROPHOTOMETRY COMBINED WITH CHEMOMETRICS; [Analisis Lemak Anjing dalam Bakso Melalui Kaedah Spektrometri Inframerah Transformasi Fourier Gabungan Bersama Kemometri] - Nurani, Laela Hayu (Elsevier B.V., 2022)
Bakso is a meatball made from beef and is very popular among Indonesians. However, the increasing number of cases of counterfeits and mixing of this meatball with dog meat in the city of Yogyakarta has caused significant unrest in several communities, especially Muslims. This study aimed to detect the fat content of dog meat in meatballs circulating in the city of Yogyakarta with an analysis using a combination of the FTIR method and the chemometric PCA. This research was designed with the making of a variety of meatballs consisting of 25 grams of beef and dog meat in calibrated samples of 0%, 20%, 40%, 60%, 80%, 90%, and 100%, as well as other ingredients, such as flour, garlic, and spices, as much as 5% of the meat weight. Three of the calibrated samples were validated and extracted with a Soxhlet extractor using the n-hexane solvent. The extracted fat was further analyzed by FTIR and processed with the Minitab19 software. The results showed that the wavenumbers ranged from 1,750 to 800 cm-1, producing various peak intensities as well as, with the PLS calibration equation y = 0.998206x + 0.999929, an R2 value of 0.9982, an RMSEC of 1.37%, an RMSEP of 1.19%, and an RMSECV of 2.32%. Furthermore, the dog and beef fats were successfully classified using the multivariate PCA. In conclusion, the analysis results showed that the FTIR spectrophotometric method combined with chemometrics was effective at classifying dog fat from other animal fats. Meanwhile, the analysis results showed that 2 out of 3 samples contained other meat contaminants. © 2022, Malaysian Society of Analytical Sciences. All rights reserved.